Climate change, transformative adaptation options, multiscale polycentric governance, and rural welfare in Oum Er-Rbia River Basin, Morocco: an empirical evaluation with policy implications - Saleth, R. M.; Ait El Mekki, A.; Amarasinghe, Upali A.; Amarnath, Giriraj; Brouziyne, Youssef (International Water Management Institute, 2023)
This Study forms part of the research under Work Package #4 (WP4) of CGIAR Research Program: Building Systemic Resilience against Climate Variability and Extremes (ClimBeR), which has the overarching goal of “setting up a bottom-up polycentric governance framework for promoting multiscale transformative adaptation options and targeted climate investments”. Consistent with this objective, this study has made an attempt to develop and empirically apply an innovative methodology that builds on the earlier analytical and empirical woks of Saleth, et al., (2007), Saleth and Dinar (2009), and Saleth, Dinar, and Frisbee (2011). This methodology is rooted in an analytical framework that delineates various possible pathways through which the impacts of climate change are transmitted ultimately on rural welfare at the grassroots level. Since these impact pathways are being characterized by various configurations of climatic, economic, policy, technical, institutional, infrastructural, and welfare-related variables, they provide an excellent operational context not only for incorporating various elements of the MPG structure within a unified context but also for evaluating their roles in mediating and enhancing the climate resilience impacts of TAOs both across regional scales and sectoral contexts. Notably, in contrast to prevalent approaches in current climate adaptation literature, the impact pathway-based analytical framework enables one to evaluate the welfare impacts of climate resilient coping and adaptation strategies in a more dynamic and interactive context. Clearly, the impact pathways, taken together, constitute the basic building blocks of the analytical framework underlying our evaluation methodology. By defining appropriate variables within relevant empirical context, these impact pathways can be formalized as an inter-related set of equations. Such an equation system can represent a mathematical analogue of the analytical framework, which is capable of being empirically estimated with appropriate data.